Doing Health, Undoing Prison: A Study with Women who have Experienced Incarceration in a Provincial Prison - Chesnay, Catherine Thérèse (Université d'Ottawa / University of Ottawa, 2016)
Studies on health and incarceration have extensively demonstrated that incarcerated women have poorer health statuses than non-incarcerated women and than incarcerated men, both as a result of confinement and of the intersection of abuse, poverty, homelessness and addiction that are simultaneously pathways to criminalisation and to poor health. Without denying the reality of disease, physical and mental suffering experienced by women in prison, this thesis conceptualizes the “problem of health in prison” by framing it as a vehicle of and effect of power relations. By studying neoliberal rationalities and technologies that constitute health, poststructuralist scholars have demonstrated how neoliberal subjects are enticed to continuously pursue health and to adhere to the imperative to be healthy. Demonstrating the intersection of neoliberal health governance and penal governance, criminologists have shown how prisons produce the subject of a healthy prisoner, who is a self-regulated woman, freely working towards her rehabilitation. Rather than studying programs, public policies and archives, this thesis innovates by examining the experiences and narratives of the subjects who are being governed and enticed to be “healthy.” Specifically, my research provides a contextualized analysis of how women negotiate and manage their health during incarceration and upon their release from prison. The first article focuses on tensions between this work’s conceptual framework and its methodology, i.e. participatory action research. An emerging literature has been building bridges between poststructuralism and participatory action research, highlighting the latter’s potential for transformative action. Using examples from participatory action research projects with incarcerated or previously incarcerated women, the article discusses how “participation” and “action” can be redefined by using a poststructuralist definition of subjectivity. The second article tackles the issue of how women “do” health in prison. Using three issues—access to health care services, smoking, and the management of body weight—the article explores how participants adopted different embodied subjectivities, which conflicted or aligned with neoliberal governmentality. It describes how, through failure to conform to neoliberal ideals of “health,” mechanisms of self-surveillance and self-regulation are relayed by feelings of guilt, shame, and anxiety, even when incarcerated women attempt to conform to imperatives to be healthy. Finally, the last article focuses on how, upon prison release, participants attempted to “undo” the imprint of penal governance on their bodies and health. Through the exploration of corporal practices, such as taking care of one’s appearance, the use of psychoactive medications, and defecating, the article shows how women attempt to “undo” prison in order to pursue health. Though these two articles focus on different periods of participants’ lives and rely on different yet related concepts—embodied subjectivities and corporal practices—the common thread between the two is to show the attempts by participants to “undo” prison from their embodied selves, and to “do” health as incited by the ethical imperatives to be healthy. The thesis concludes with a discussion about the pursuit of health, and its effects on the populations deemed as “at risk” and “unhealthy.”
Keywords: Participatory action research; prison; health; incarceration; women; subjectivity; embodiment; poststructuralism